Interaktif 3d Level Design Game dengan Tema Nusantara pada Blueprint Unreal Engine 4 - Mochammad Qoirul Aziz; Maulana Rizqi (Journal of Animation and Games Studies, 2023)
The development of the gaming world has undergone very rapid progress, and we can see that the platforms for playing games have become more flexible. Looking at current trends and smartphone technology, the mobile gaming industry will become very popular due to the ease of use of the platform. In this research, the method used is Blueprint Visual Scripting, using this method allows for the development of games without coding. The purpose of this research is to design an interactive level design in a game by bringing the latest technology from a game engine that produces a prototype design of the map and interaction components in the game.